The RsmA RNA-Binding Proteins in Pseudomonas syringae Exhibit Distinct and Overlapping Roles in Modulating Virulence and Survival Under Different Nutritional Conditions - Liu, Jun; Yu, Menghao; Ge, Yixin; Tian, Yanli; Hu, Baishi; Zhao, Youfu (Frontiers in Plant Science, 2021)
The post-transcriptional regulator RsmA globally controls gene expression in bacteria. Previous studies showed that RsmA2 and RsmA3 played critical roles in regulating type III secretion system (T3SS), motility, syringafactin, and alginate productions in Pseudomonas syringae pv. tomato strain DC3000 (PstDC3000). In this study, we investigated global gene expression profiles of the wild-type PstDC3000, the rsmA3 mutant and the rsmA2/A3 double mutant in the hrp-inducing minimum medium (HMM) and King’s B (KB) medium. By comparing the rsmA2/A3 and rsmA3 mutants to PstDC3000, a total of 1358 and 1074 differentially expressed genes (DEGs) in HMM, and 870 and 1463 DEGs in KB were uncovered, respectively. When comparing the rsmA2/A3 mutant with the rsmA3 mutant, 277 and 741 DEGs in HMM and KB, respectively, were revealed. Transcriptomic analysis revealed that the rsmY, rsmZ, and rsmX1-5 non-coding small RNAs (ncsRNAs) were positively affected by RsmA2 and RsmA3; while RsmA3 positively regulates the expression of the rsmA2 gene and negatively regulates both rsmA1 and rsmA5 gene expression. Comparative transcriptomic analysis showed that RsmA2 and RsmA3 synergistically influenced expression of genes involved in T3SS and alginate biosynthesis in HMM and chemotaxis in KB. RsmA2 and RsmA3 inversely affected genes involved in syringafactin production in HMM and ribosomal protein biosynthesis in KB. In addition, RsmA2 played a major role in influencing genes involved in sarcosine and thiamine biosynthesis in HMM and in mannitol and phosphate metabolism in KB. On the other hand, genes involved in fatty acid metabolism, cellulose biosynthesis, signal transduction, and stress responses were mainly impacted by RsmA3 in both HMM and KB; whereas RsmA3 played a major role in controlling genes involved in c-di-GMP, phosphate metabolism, chemotaxis and capsular polysaccharide in HMM. Furthermore, regulation of syringafactin production and oxidative stress by RsmA2 and RsmA3 was experimentally verified. Our results suggested the potential interplay among the RsmA proteins, which exhibit distinct and overlapping roles in modulating virulence and survival in P. syringae under different nutritional conditions.